Giving Career Information Service to Enhance Students’ Self-sufficiency in Selecting Careers - Nashruddin, Nashruddin; Sakkir, Geminastiti; Aisyah, Sitti; Apriyawanto, Apriyawanto (Universitas PGRI Madiun, 2023)
The present research aimed at (1) knowing the implementation of the career information service towards students’ self-sufficiency of selecting careers, and (2) finding the effect of career information service on the self-sufficiency of selecting careers. This study applied quasi-experimental method with 25 students as the participants. It had a hypothesis statement of cause and effect on a sort of changing for comparing two or more groups. Based on the result, the null hypothesis is rejected because it exists the outside limit of the null hypothesis acceptance. In line with that finding, it is concluded that the students’ self-reliance of selecting career before the career information service is given; no students have self-reliance of choosing either a high career or a higher career. This study develops the significant role of career information to facilitate students for choosing careers in their future life.